Investigation of physical activity level and life quality of elementary school teachers under the Ministry of National Education - PINAR, SALİH; PINAR, YELİZ (ELSEVIER SCIENCE BV, 2014)
The aim of this study was to investigate the physical activity level and life quality of teachers who work in provincial elementary schools of the national education ministry, Antalya. Totally 160 teachers (78 female, 82 male) participated in this study. The average age of the teachers was 41,99+6,35 years for female, and 44,45+6,71 years for male. The waist and hip circumference, body height, and weight of subject were measured. Physical Activity Levels (PAL) of subjects was evaluated by using International Physical activity Questionnaires (IPAQ). SF-36 Quality Life Questionnaires was used for determining subjects' life quality. It was found that the average energy consumption of teachers was 1608,50 +/- 2026,11 MET-min. week(-1). On the other hand, male teachers were higher (p<0.01) and heavier (p<0,05) than their female colleagues in body height and weight, respectively. Thus, BMI's scores of male teachers were higher than their female colleagues (p<0,05). On the one hand, women had more MET scores than men in many activities; on the other hand men had more scores in physical role in this study. (C) 2013 The Authors. Published by Elsevier Ltd. Selection and/or peer-review under responsibility of Academic World Education and Research Center.
Keywords: Physical activity; IPAQ; MET; BMI; RELIABILITY